2022
DOI: 10.1093/jac/dkac001
|View full text |Cite
|
Sign up to set email alerts
|

Intranasally administered S-MGB-364 displays antitubercular activity and modulates the host immune response to Mycobacterium tuberculosis infection

Abstract: Background Previously, we evaluated the intracellular mycobactericidal activity of the minor groove binder, S-MGB-364 against the clinical Mycobacterium tuberculosis (Mtb) strain HN878 in macrophages. Objectives To assess the mycobactericidal activity of S-MGB-364 in Mtb-infected mice. Further, we investigated a plausible DNA binding mechanism of action of S-MGB-364. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The DNA oligomer itself, 5′-CGCATATATGCG-3′, was shown by nMS to have both single-stranded DNA [SS] in charge states 4- and 3-, and double-stranded DNA [DS] in charge states 5- and 4- ( Figure 4 ), which is typical of these experiments [ 11 ]. The nMS of DNA sequence 5′-CGCATATATGCG-3′ in the presence of S-MGB-219 showed that it bound to double-stranded DNA as a dimer [DS+2M] in charge states 5- and 4- ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The DNA oligomer itself, 5′-CGCATATATGCG-3′, was shown by nMS to have both single-stranded DNA [SS] in charge states 4- and 3-, and double-stranded DNA [DS] in charge states 5- and 4- ( Figure 4 ), which is typical of these experiments [ 11 ]. The nMS of DNA sequence 5′-CGCATATATGCG-3′ in the presence of S-MGB-219 showed that it bound to double-stranded DNA as a dimer [DS+2M] in charge states 5- and 4- ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 89%
“…The test oligonucleotide, d(5′-CGCATATATGCG-3′), is designed to identify binders to AT-rich regions; however, to expand the scope of the thermal binding assay, S-MGB-3 and S-MGB-219 were also investigated using genomic DNA from salmon, using S-MGB-3 as a comparator ( Figure 3 ). Salmon is commonly used as an easily accessible, cheap source of genomic DNA, and has been used in early-stage target-binding studies of S-MGBs previously [ 11 ]. S-MGB-219 had a substantial T m increase of 8.0 °C, compared to 12.6 °C for S-MGB-3 , the latter of which is in line with previous work on S-MGB-3 (manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S-MGBs are analogues of the natural product distamycin, which target multiple sites on bacterial DNA and are active against M. tuberculosis. , We demonstrate that decrease in intracellular mycobacteria corresponds with a greater association of mycobacterial phagosomes with lysosomal markers. Finally, the efficacy of C13 alone and in combination with the antibiotics and compounds was also demonstrated in an in vivo model of infection using larvae of the waxworm Galleria mellonella.…”
mentioning
confidence: 99%
“…Their favorable cytotoxicity profiles to mammalian cells give them selectivity indices that make them suitable for development as novel drugs. This has enabled extensive in vitro and several in vivo experiments to provide proof of concept for S-MGBs as a novel class of anti-infective agent against bacterial, fungal, viral, and parasitic infections. One of these compounds, MGB-BP-3 (Figure ) has successfully completed Phase IIa clinical trials for the treatment of Clostridioides difficile associated disease (NCT03824795). MGB-BP-3 also has potent (<1 μg/mL) antibacterial activity against methicillin-resistant and methicillin-susceptible Staphylococcus spp., Streptococcus spp., and vancomycin-resistant and vancomycin-susceptible Enterococcus spp .…”
mentioning
confidence: 99%